STRATEGI KREATIF MENGGUNAKAN ICE BREAKING UNTUK MENINGKATKAN MOTORIK HALUS DI TAMAN KANAK-KANAK - Hendrawati, Emi; Nurhafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the fine motor skills of early childhood learners through the implementation of a creative ice-breaking strategy in learning activities. The study was motivated by the low level of children’s fine motor skills, as reflected in the limited coordination of hand and finger movements during classroom activities. This research employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles that included planning, action, observation, and reflection stages. The participants were early childhood learners enrolled in a preschool learning group. Data were collected through observation, documentation, and child development assessments. The data were analyzed using descriptive quantitative techniques by calculating the percentage of children's fine motor skill achievement in each cycle. The findings indicated that the implementation of a creative ice-breaking strategy significantly improved children's fine motor skills. In the pre-action stage, the achievement level was 40%, which increased to 66% in Cycle 1 and reached 87% in Cycle 2. The improvement demonstrates that creatively designed ice-breaking activities can create an enjoyable learning environment, enhance concentration, motivation, and active participation, and provide effective stimulation for fine motor development. Therefore, the creative use of ice-breaking strategies was proven effective in improving the fine motor skills of early childhood learners and can be utilized as an innovative learning alternative in early childhood education settings.